Antibiogram of Bacteria Isolated from Bloodstream Infection-Suspected Patients at the University of Gondar Comprehensive Specialized Hospital in Northwest Ethiopia: A Retrospective Study - Minichil Worku; Tigist Molla; Desie Kasew; Muluneh Assefa; Alene Geteneh; Melak Aynalem; Mucheye Gizachew; Sirak Biset (International Journal of Microbiology)
Background. Bacterial bloodstream infections (BSIs) are the leading cause of sepsis-related morbidity and mortality worldwide. The emergence and spread of antimicrobial resistance (AMR) in bacteria is also a growing global concern. As a result, data on bacterial profile and their antibiogram are essential for strategies to contain drug resistance, improve the quality of patient care, and strengthen health systems. Methods. Retrospective data from bacteriological results of blood samples of BSI-suspected patients from 2018 to 2021 were collected using a data collection sheet. Standard bacteriological techniques were followed during sample collection, culture preparation, bacterial identification, and antibiotic susceptibility testing (AST). We used Epi Info version 7 to enter and clean the data and then exported it to SPSS version 26 for analysis. Logistic regression models were used to measure the association between variables. A p value <0.05 with a 95% confidence interval was considered as statistically significant. Result. Of the total 2,795 blood culture records, 455 (16.3%) were culture positive for bacteria, with Klebsiella pneumoniae (26%) and Staphylococcus aureus (24.6%) being the leading isolates. The isolates were highly resistant to common antibiotics, with more than 80% of them being resistant to ceftriaxone and penicillin. Moreover, about 43% of isolates were multidrug resistant (MDR), with Klebsiella pneumoniae (65.5%), Acinetobacter species (56.7%), and Citrobacter species (53.8%) being the most common MDR isolates. Age and diagnosis year were significantly associated with the presence of bacterial BSIs (p value <0.05). Conclusion. Bacterial BSI and AMR were growing concerns in the study area. Bacteremia was more common in children under the age of five, and it decreased as the patient’s age increased. The alarming rate of AMR, such as MDR blood isolates, calls for periodic and continuous monitoring of antibiotic usage in the study area.